Decision of Comprehensive Development Level of Reclaimed Water Based on Improved Catastrophe Theory: A Case Study in Yunnan Province, China - Huang, Xin; Qiu, Lin (Frontiers in Environmental Science, 2022)
In order to utilize reclaimed water resources reasonably and efficiently, it is necessary to strengthen the evaluation of reclaimed water. However, a major problem with traditional reclaimed water assessment methods is it mostly focuses on a single aspect. In this paper, an evaluation model of comprehensive development level of reclaimed water which consists of four layers with three criteria, and 17 indicators is established. An improved catastrophe theory was utilized to obtain diversely distributed adjusted assessment values of comprehensive development level of reclaimed water. Finally, the single factor sensitivity analysis was performed on above-mentioned model, and the sensitivity sequence of each indicator was determined according to the comprehensive development ability of reclaimed water. The results showed that, 1. In Yunnan province, the comprehensive development level of reclaimed water grew steadily from 2012 to 2015, but declined in 2016. Water deficiency was the most sensitive factor followed by waste water discharge, grade 1 B treatment level and Construction impact as the secondary sensitive factors. 2.Compared with the fuzzy comprehensive evaluation method, the improved catastrophe evaluation method has the advantages of rigorous theory, concise model and simple calculation, and the decision result is more objective and reliable.